Advancing Carvedilol’s Therapeutic Impact: A Study On Solid Dispersion Capsules for Improved Efficacy: Pharmaceutical sciences- Pharmaceutics - Kumar, Pavan; PG, Subhash; Abdul Ahad, Hindustan; Dhamala, Pawan; D, Suprith (International Journal of Life Science and Pharma Research, 2024)
This study aimed primarily to improve and evaluate the dissolution rate of Carvedilol by employing a solid dispersiontechnique with β-Cyclodextrin as the carrier. Three distinct methods were utilized to create Carvedilol-containing soliddispersions: The Kneading method, Physical mixture, and Solvent evaporation method. These methods incorporated β-Cyclodextrin at varying drug-carrier ratios (1:1, 1:2, and 1:3). The initial phase encompassed pre-formulation assessments, includingthe establishment of a calibration curve, determination of lambda maximum, melting point determination, investigation of solubilityin different solvents, and evaluation of Carvedilol-polymer compatibility through FTIR analysis. Subsequent post-formulationanalyses included tests for weight variation, Carvedilol content, lock length, moisture permeation, disintegration time, in-vitrodissolution, and stability. The results of the pre-formulation tests were consistent with established references. FTIR analysisrevealed no interactions between the Carvedilol and the carrier. Carvedilol content, weight variation, and disintegration time testsmet the permissible limits outlined in IP standards. Both lock length and moisture permeation tests conformed to the criteria.However, due to Carvedilol’s limited solubility, dissolution was inadequate. Among the in-vitro dissolution profiles, the "KN3"formulation, prepared using the Kneading method with a 1:3 ratio of Carvedilol to Carrier, employing β-Cyclodextrin as thecarrier, exhibited superior discharge at 94.671%, outperforming other preparation methods.